2013
DOI: 10.1177/2158244013501330
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Counseling Professionals/Paraprofessionals Attitudes Toward Adolescent Sexual Offenders

Abstract: One hundred thirty-three counseling professionals/paraprofessionals were recruited from adolescent residential treatment programs located in Michigan. Participants were assessed using the Community Attitudes Toward Sex Offender Scale (CATSO). Of the participants, 32.3% (n = 43) of the participants were female and 67.7% (n = 90) were male. Years of experience working directly with adolescent sexual offenders of participants ranged from 0 to 18 years (M = 2.48 years, SD = 3.48). The number of months participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
4
10
0
Order By: Relevance
“…Public samples have been found to score higher on the CATSO than professional populations (Malinen et al, 2014;Shackley et al, 2013), with other factors influencing scores being experience of working with sex offenders (experience is correlated with lower scores; Jones, 2013) and educational attainment (lower educational attainment is correlated with higher scores; Malinen et al, 2014). These findings corroborate previous research into attitudes toward sex offenders using different measures (e.g.…”
Section: Previous Uses Of the Catsosupporting
confidence: 82%
See 1 more Smart Citation
“…Public samples have been found to score higher on the CATSO than professional populations (Malinen et al, 2014;Shackley et al, 2013), with other factors influencing scores being experience of working with sex offenders (experience is correlated with lower scores; Jones, 2013) and educational attainment (lower educational attainment is correlated with higher scores; Malinen et al, 2014). These findings corroborate previous research into attitudes toward sex offenders using different measures (e.g.…”
Section: Previous Uses Of the Catsosupporting
confidence: 82%
“…The CATSO has been utilized as either a dependent or control measure in a number of studies since its inception, with scores being similar (~50) across a range of samples, including counselors working with sexually abusive adolescents (Jones, 2013), criminology undergraduates (Marteache, 2012), and a cohort of the Australian public (Shackley et al, 2013). Public samples have been found to score higher on the CATSO than professional populations (Malinen et al, 2014;Shackley et al, 2013), with other factors influencing scores being experience of working with sex offenders (experience is correlated with lower scores; Jones, 2013) and educational attainment (lower educational attainment is correlated with higher scores; Malinen et al, 2014).…”
Section: Previous Uses Of the Catsomentioning
confidence: 99%
“…score that can range from 18-108 (higher scores indicate more negative views about sexual offenders). In a range of studies, the CATSO has demonstrated acceptable levels of internal consistency (α = 0.74; Church et al, 2008;Conley, Hill, Church, Stoeckel, & Allen, 2011;Jones, 2013;Malinen, Willis, & Johnston, 2014;Shackley, Weiner, Day, & Willis, 2014;Shelton, Stone, & Winder, 2013). Church et al's (2008) initial factor analyses of the CATSO data identified an underlying four-factor structure, with these factors being labeled 'Social Isolation', 'Capacity to Change', 'Dangerousness', and 'Deviancy'.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Scores for each of the items are summed to provide a composite CATSO score that can range from 18-108 (higher scores indicate more negative views about sexual offenders). In a range of studies, the CATSO has demonstrated acceptable levels of internal consistency (α > 0.70; Church et al, 2008;Conley, Hill, Church, Stoeckel, & Allen, 2011;Jones, 2013;Malinen, Willis, & Johnston, 2014;Shackley, Weiner, Day, & Willis, 2014;Shelton, Stone, & Winder, 2013). Church et al's (2008) initial factor analyses of the CATSO data identified a four-factor structure underpinning the scale, with these being labeled 'Social Isolation', 'Capacity to Change', 'Dangerousness', and 'Deviancy'.…”
Section: Current Approaches To Measuring Attitudes To Sexual Offendersmentioning
confidence: 99%